SURVEI TINGKAT KEMAMPUAN VO2MAX PADA ATLET SEPAKBOLA DI LSS (LUWU SOCCER SCHOOL) - Muh. Rizky Agung Ramadhan; Rusli Rusli; Andi Atssam Mappanyukki (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
The formulation of the problem in this research is How to Survey the Ability Level of V02MAX on Football Athletes at LSS (Luwu Soccer School). The type of research that will be used in this study is descriptive quantitative analysis. In this research design, research subjects were selected by purposive sampling based on certain characteristics for into a whole existing sample, research so that research subjects are homogeneous. While data analysis using SPSS 21 by using descriptive test, normality test and hypothesis test. Based on the results of the analysis of the V02MAX Ability Level Survey on Football Athletes at LSS (Luwu Soccer School) from the data percentage test, namely 6 people who fall into the Very Less criteria with a percentage of 33%. 4 people who fall into the Less criteria with a percentage of 22%, 4 0people who fall into the sufficient criteria with a percentage of 22%. and 4 people who fall into the Good criteria with a percentage of 22%. overall sample 18.